The New CPC and the maintenance action: insecurity due to the systematic expansion of the legal concept of family and kinship as a result of modern assisted reproduction technologies (Revista do Tribunal Regional Federal da 3ª Região, 2016)
This paper deals with the subject of alimony lite under the new Brazilian Civil Procedural Code. It analyses the difficulties and uncertainties that might arise from the current broad concepts of family and kinship, which derive from the modern techniques of human assisted reproduction.
Keywords: CPC 2015; alimony lite; duty to pay alimony; bonds of kinship; family relationship; legal status of the child